Electrochemistry of Surfactants - Schulz, Eduardo Nicolás (2017)
The application of different electrochemical techniques to surfactant systems, namely polarography and cyclic voltammetry, differential capacitance, chronocoulometry and electrochemical impedance spectroscopy, is reviewed.